Social Media Use Among the Elderly: Balancing Benefits and Risks - Srivastava, Kajal; Rathod, Hetal K (Indian Journal of Community Health, 2025)
In India, a senior citizen is any person who is sixty years of age or older(1). Excessive or compulsive obsession, cravings, or behaviors related to computer use and internet access, together with the accompanying distress or impairment, are characteristics of internet addiction. Over the past few years, as computer and internet access has increased, internet addiction has drawn more attention from researchers, physicians, and the media(2). With more than 900 million internet users and the second-largest e-market in the world after China, India boasts a sizable user base and a growing trend of internet usage. At over 50%(3), the nation's internet penetration rate still falls short of the global average. Elderly people can also benefit from social media in other ways, such as increased social connectivity, which gives them a sense of belonging by enabling them to reconnect with old acquaintances and family members and lessen feelings of loneliness and isolation. It provides cognitive stimulation through activities such as reading articles, seeing films, and participating in online discussion forums, thereby informing individuals about current events and trends, while facilitating lifelong learning and cognitive engagement. Major advantage of social media is that it helps people connecting with known and unknown people distantly which gives them sense of connected to World. This becomes more significant during illness when people are more restricted to go out and meet people so social media comes for their rescue. As more and more social media platforms are also available to people so elderly wants to spend more time on their mobile operating different sites like facebook, Instagram, twitter, linkedin etc. Irony is that physical activity and warmness in meeting people has subsided due to overuse of this harmful addiction.